Preparing business students for workplace reality: using global virtual teams in logistics and SCM education - Trautrims, Alexander; Defee, Cliff; Farris, Ted (Emerald, 2016)
Purpose: This paper presents and examines the use and effects of global virtual teams as a tool in the logistics and supply chain management classroom to prepare students in a simulation environment for the demands of their future careers in the profession. Design/methodology/approach: Literature of logistics and supply chain management education is combined with streams from management learning literature. The way the tool of global virtual teams was applied is explained, followed by an analysis of quantitative and qualitative participant response data. From the data analysis the effects of individual factors in the design and application of the global virtual team are isolated and recommendations are extracted for future use of the tool. Findings: The paper finds that the application of global virtual teams helped participating students to develop the management skills required for a career in logistics and supply chain management. Although students perceived the international nature and the lose frame provided by the tool as challenges, most learning effects were caused by these challenges. The paper also shows that the set up by the involved educators is crucial for the learning effect in particular towards similar weights of the assessments and the number of group members from each geographical area. Research limitations/implications: The paper does not examine all potentially amendable factors but focusses on those that were seen as relevant and practically achievable under the available resources to ensure the tool can be easily scaled up by adding further institutions and participants. Originality/value: The paper is the first application of global virtual teams in logistics and supply chain management education. It provides the theoretical foundations and rationale for its application and is relevant to educators by giving them access to this tool for improvement of their students’ career preparedness.